Decorative sheet
By forming a specific irregular structure on the surface of the decorative sheet and using ion radiation curing resin and microparticles, the problem that decorative sheets are difficult to achieve low gloss and wetness is solved, and its scratch resistance, stain resistance and weather resistance are improved.
Patent Information
- Application Number
- JP2024192154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-09
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
AI Technical Summary
It is difficult for existing decorative sheets to achieve low gloss and wetness effects at the same time, and they also have excellent scratch resistance and stain resistance.
By forming a specific irregular structure on the surface of the decorative sheet, including the raised portion of the surface protective layer, the thickness and irregularity ratio of the surface protective layer are controlled, and a specific type of ion radiation curing resin and microparticles are used to form a surface texture with a low gloss and wet feeling.
It achieves a low-gloss decorative effect, while providing a slippery touch experience, and improves the scratch resistance and stain resistance of the decorative sheet, enhancing its weather resistance and processing properties.
Smart Images

Figure 2025013431000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a decorative sheet. The decorative sheet can be used, for example, for the interior and exterior decoration of buildings, and for surface decoration of fittings, furniture, construction materials, flooring materials, and the like. [Background technology]
[0002] In recent years, as shown in Patent Document 1, many decorative sheets using olefin resins (e.g., polypropylene sheets) have been proposed as alternatives to decorative sheets made of polyvinyl chloride, which are of concern in terms of environmental protection. By not using vinyl chloride resin, these decorative sheets suppress the generation of toxic gases and the like during incineration.
[0003] Decorative sheets are widely used in architectures by laminating the surfaces of wood, wood boards, metal sheets, non-flammable boards, paper substrates, or resin substrates with adhesives to give the surfaces design and durability. The design can be selected according to requirements and applications, from patterns such as wood grain or stone grain formed using various printing methods to plain surfaces without any patterns. Similarly, the gloss of the surface is also an important item for design, and can be selected according to requirements and applications, from high gloss like a mirror to low gloss with no reflection at all. Another important function of decorative sheets, in addition to design, is durability. Durability is a comprehensive evaluation of scratch resistance, stain resistance, and whether these are guaranteed continuously for a long period of time. Decorative sheets are used for architectural interior materials for houses and public facilities, architectural exterior materials such as entrance doors, surface materials for fixtures, and surface materials for home appliances. For this reason, they are exposed to direct sunlight and wind and rain every day, and are required to have extremely high weather resistance.
[0004] To provide durability, a surface protective layer is generally formed on the outermost surface of the decorative sheet. Also, in order to adjust the aforementioned glossiness, particularly to achieve low glossiness, a gloss regulator (matt additive) is generally added to the surface protective layer. As such, a decorative sheet that takes into consideration design (low gloss), scratch resistance, and stain resistance is, for example, the decorative sheet described in Patent Document 2.
[0005] On the other hand, Patent Documents 3 to 7 propose a method for producing a low-gloss decorative sheet by forming wrinkles using excimer light with a wavelength of less than 200 nm. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3271022 [Patent Document 2] JP 2019-119138 A [Patent Document 3] International Publication No. 2021 / 201105 [Patent Document 4] Patent Publication No. 2022-008024 [Patent Document 5] International Publication No. 2022 / 054644 [Patent Document 6] International Publication No. 2022 / 054645 [Patent Document 7] International Publication No. 2022 / 054646 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a decorative sheet which has low gloss and gives a moist feel to the touch. [Means for solving the problem]
[0008] According to one aspect of the present invention, a substrate fabric layer and a surface protective layer provided on one surface of the substrate fabric layer are provided, and a concave-convex structure including a plurality of ridge-like portions each protruding in a ridge shape is provided on the surface of the surface protective layer, and the concave-convex structure of the surface protective layer has a ratio Rdc / t of a cut level difference Rdc to a thickness t of the surface protective layer of 0.15 to 0.44, and the thickness t of the surface protective layer is 2 μm to 18 μm, and an absorption spectrum obtained by Fourier type infrared spectroscopy measurement of the surface protective layer has a wavelength of 1085 to 1105 cm. -1 Maximum value in the wavenumber range of I 1095 and 1715 to 1735 cm -1 Maximum value in the wavenumber range of I 1725 Comparison with I 1095 / I 1725 is 0.65 or more.
[0009] According to another aspect of the present invention, there is provided a decorative sheet according to the above aspect, wherein the gloss of the surface protective layer is less than 10.0.
[0010] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the ratio Rdc / t is equal to or greater than 0.15 and equal to or less than 0.31.
[0011] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the ratio Rdc / t is 0.15 or more and 0.25 or less.
[0012] According to yet another aspect of the present invention, the ratio I 1095 / I 1725 The decorative sheet according to any of the above aspects is provided, wherein the σ is 3.5 or less.
[0013] According to yet another aspect of the present invention, the ratio I 1095 / I 1725 is 0.7 or more. According to yet another aspect of the present invention, the ratio I 1095 / I 1725 is 0.85 or more.
[0014] According to yet another aspect of the present invention, the ratio I 1095 / I 1725 The decorative sheet according to any of the above aspects is provided, wherein the σ is 2.2 or less. According to yet another aspect of the present invention, the ratio I 1095 / I 1725 The decorative sheet according to any of the above aspects is provided, wherein the σ is 1.3 or less.
[0015] According to yet another aspect of the present invention, there is provided a decorative sheet relating to any of the above aspects, wherein the surface protection layer comprises a cured resin and particles, the particles having an average particle size of 3 μm or more and 11 μm or less, and the particles are contained in the surface protection layer in an amount of 3 parts by mass or more and 11 parts by mass or less per 100 parts by mass of the resin.
[0016] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the resin is an ionizing radiation curable resin.
[0017] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the resin is an acrylate.
[0018] According to yet another aspect of the present invention, there is provided a decorative sheet according to any of the above aspects, wherein the resin is a trifunctional acrylate containing a repeating structure, and the number of repetitions of the repeating structure is 3 or more and 20 or less.
[0019] According to yet another aspect of the present invention, there is provided a decorative sheet according to any of the above aspects, wherein the resin is a tetrafunctional acrylate containing a repeating structure, and the number of repetitions of the repeating structure is 20 or more and 35 or less.
[0020] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, further comprising a design layer between the base layer and the surface protective layer.
[0021] According to yet another aspect of the present invention, there is provided a decorative material comprising a decorative sheet according to any one of the above aspects and a substrate to which the decorative sheet is attached. Effect of the Invention
[0022] According to the present invention, it is possible to provide a decorative sheet that has low gloss and provides a moist feel to the touch. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a cross-sectional view of a decorative material including a decorative sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a decorative material including a decorative sheet according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of the surface protective layer of the decorative sheet of FIG. 1 and FIG. [Figure 4] FIG. 4 is a microscope image of the surface protective layer of a decorative sheet according to one example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The configuration of the decorative sheet according to the embodiment of the present invention will be described below with reference to the drawings. The embodiment described below is a more specific embodiment of any of the above aspects. The items described below can be incorporated into each of the above aspects alone or in combination.
[0025] In the drawings referred to below, elements having the same or similar functions are given the same reference numerals, and duplicated explanations are omitted. In addition, the drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc. differ from the actual ones.
[0026] The embodiments described below are merely examples of configurations for embodying the technical idea of the present invention, and the technical idea of the present invention does not limit the materials, shapes, structures, etc. of the components to those described below. The technical idea of the present invention can be modified in various ways within the technical scope defined by the claims.
[0027] <1> Decorative materials and decorative sheets Fig. 1 is a cross-sectional view of a decorative material including a decorative sheet according to one embodiment of the present invention. Fig. 2 is a cross-sectional view of a decorative material including a decorative sheet according to another embodiment of the present invention. Fig. 3 is a cross-sectional view of the surface protective layer of the decorative sheet of Figs. 1 and 2. Fig. 4 is a micrograph of the surface protective layer of a decorative sheet according to one example of the present invention.
[0028] The cross section shown in Fig. 3 is a cross section taken along the thickness direction of the surface protective layer. The micrograph in Fig. 4 is a plan view taken with a laser microscope (OLS-4000 manufactured by Olympus Corporation).
[0029] The decorative material 11 shown in Figures 1 and 2 includes a substrate B and a decorative sheet 1 attached thereto. Here, the decorative material 11 is a decorative board. The decorative board may be a flat plate, or may be curved or folded. The decorative material 11 may have a shape other than a plate.
[0030] Here, the substrate B is a plate material. The plate material is, for example, a wood board, an inorganic board, a metal plate, or a composite board made of a plurality of materials. The substrate B may have a shape other than a plate.
[0031] The decorative sheet 1 shown in Fig. 1 has a pattern layer 3 and a surface protective layer 5 provided in this order from the original fabric layer 2 side on one surface, i.e., the front side, of an original fabric layer 2, and a primer layer 6 provided on the other surface (i.e., the surface facing the substrate B) of the original fabric layer 2. In Fig. 1, one or more of the pattern layer 3 and the primer layer 6 may be omitted.
[0032] In addition, the decorative sheet 1 shown in FIG. 2 has a pattern layer 3, an adhesive resin layer 4b, a transparent resin layer 4, and a surface protection layer 5 provided in this order from the original fabric layer 2 on one surface, i.e., the front side, of the original fabric layer 2, and a primer layer 6 provided on the other surface of the original fabric layer 2 (i.e., the surface facing the substrate B). Here, the transparent resin layer 4 is provided with an embossed uneven pattern (embossed pattern 4a). In FIG. 2, one or more of the pattern layer 3, adhesive resin layer 4b, transparent resin layer 4, and primer layer 6 may be omitted. Also, the embossed pattern 4a may not be provided.
[0033] Furthermore, in order to meet the requirements for scratch resistance, etc., at least one of the transparent resin layer 4 and the surface protective layer 5 may be laminated in multiple layers. In addition, in consideration of the adhesion between each layer, other known layers may be arranged. In addition, a concealing layer (not shown) or the like may be appropriately provided between the base layer 2 and the primer layer 6.
[0034] Next, each layer constituting the decorative sheet 1 will be described.
[0035] <1.1> Original layer As the raw fabric layer 2, for example, any material selected from paper, synthetic resin, synthetic resin foam, rubber, nonwoven fabric, synthetic paper, metal foil, etc. can be used. Examples of paper include tissue paper, titanium paper, resin-impregnated paper, etc. Examples of synthetic resin include polyethylene, polypropylene, polybutylene, polystyrene, polycarbonate, polyester, polyamide, ethylene-vinyl acetate copolymer, polyvinyl alcohol, acrylic, etc. Examples of rubber include ethylene-propylene copolymer rubber, ethylene-propylene-diene copolymer rubber, styrene-butadiene copolymer rubber, styrene-isoprene-styrene block copolymer rubber, styrene-butadiene-styrene block copolymer rubber, polyurethane, etc. Examples of nonwoven fabric include organic and inorganic nonwoven fabric. Examples of metals of the metal foil include aluminum, iron, gold, silver, etc. In addition, the raw fabric layer 2 may be a sheet made of the same resin composition as the transparent resin layer 4. In this case, the raw fabric layer 2 is obtained by forming a resin material or a resin composition into a film. Examples of the molding method include calendar molding and extrusion molding.
[0036] The raw fabric layer 2 preferably has a colored layer made of a synthetic resin mixed with an inorganic pigment, and a skin layer made of a synthetic resin. The thickness of the skin layer is preferably 3 μm or more and 20 μm or less, and the ratio of the thickness of the skin layer to the colored layer is preferably 1:6 to 1:50. When the raw fabric layer 2 is formed by a co-extrusion method, if the colored layer is the outermost layer, the pigment component contained in the colored layer will blade and contaminate the T-die of the extruder and the roll during transportation, so it is preferable that the outermost layer is a skin layer that does not contain a pigment. It is preferable to provide a skin layer on both sides of the colored layer. If the skin layer is made thicker and its ratio to the colored layer is increased, the ratio of the colored layer will decrease, and the hiding power will decrease, which is not preferable.
[0037] In addition, the thickness of the raw fabric layer 2 is preferably 50 μm or more and 150 μm or less. If the thickness of the raw fabric layer 2 is less than 50 μm, the performance of covering the unevenness of the base (unevenness) decreases. On the other hand, if the thickness of the raw fabric layer 2 exceeds 150 μm, problems such as whitening and cracking may occur during bending.
[0038] (Inorganic pigments) The inorganic pigment may be a known inorganic pigment, such as titanium oxide, which is used to provide hiding properties. The raw fabric layer 2 plays a role in hiding the pattern of the substrate B. In order to obtain the hiding properties required from the viewpoint of the design of the decorative sheet 1, the light transmittance is preferably 40% or less. If the hiding properties are low, the pattern of the design layer 3 and the pattern of the substrate B will be mixed, which is not preferable. By containing an inorganic pigment, a decorative sheet 1 with good hiding properties can be obtained. The mixed amount of the inorganic pigment is preferably 5 parts by mass or more and 50 parts by mass or less, based on 100 parts by mass of the resin material. If the mixed amount of the inorganic pigment is small, the hiding properties will be poor, and if the mixed amount is 50 parts by mass or more, embrittlement of the raw fabric layer 2 will occur, which is not preferable. The inorganic pigment contained is not particularly limited, but examples thereof include natural inorganic pigments and synthetic inorganic pigments. Examples of natural inorganic pigments include earth pigments, calcined earth, and mineral pigments. Examples of synthetic inorganic pigments include oxide pigments, hydroxide pigments, sulfide pigments, silicate pigments, phosphate pigments, carbonate pigments, metal powder pigments, carbon pigments, etc. As the synthetic inorganic pigment, a mixed pigment of one or more of natural inorganic pigments and synthetic inorganic pigments may be used. As the synthetic inorganic pigment, an organic pigment such as carbon black may be used in combination.
[0039] Furthermore, additives such as fatty acid metal salts may be added to the inorganic pigment in order to improve dispersibility and extrusion suitability.
[0040] When a substrate having an inactive surface such as an olefin-based substrate is used as the raw fabric layer 2, it is desirable to subject the front and back surfaces of the raw fabric layer 2 to corona treatment, plasma treatment, ozone treatment, electron beam treatment, ultraviolet treatment, dichromate treatment, etc.
[0041] <1.2> Picture layer A pattern layer 3 for adding a pattern to the decorative sheet 1 can be provided on the surface of the base fabric layer 2. The pattern may be a wood grain pattern, a stone grain pattern, a sand grain pattern, a tiled pattern, a brickwork pattern, a cloth pattern, a leather-stained pattern, a geometric figure, or the like.
[0042] Furthermore, a base solid ink layer (not shown) may be provided between the base layer 2 and the pattern layer 3 depending on the level of the desired design. The base solid ink layer is provided so as to cover the entire surface of the base layer 2. The base solid ink layer may be multi-layered, having two or more layers, as necessary for hiding properties, etc. Furthermore, the pattern layer 3 may be formed by laminating the number of plates required to express the desired design. In this way, the pattern layer 3 and the base solid ink layer may be combined in various ways depending on the desired design, that is, the design to be expressed, but are not particularly limited.
[0043] The constituent materials of the base solid ink layer and the design layer 3 are not particularly limited. For example, printing inks or coating agents obtained by dissolving or dispersing a matrix and a colorant such as a dye or pigment in a solvent can be used as the constituent materials of the base solid ink layer and the design layer 3. As the matrix, various synthetic resins such as oil-based nitrocellulose resin, two-liquid urethane resin, acrylic resin, styrene resin, polyester resin, urethane resin, polyvinyl resin, alkyd resin, epoxy resin, melamine resin, fluorine resin, silicone resin, and rubber resin, or mixtures or copolymers thereof can be used. In addition, as the colorant, inorganic pigments such as carbon black, titanium white, zinc oxide, red oxide, yellow lead, Prussian blue, and cadmium red, organic pigments such as azo pigments, lake pigments, anthraquinone pigments, phthalocyanine pigments, isoindolinone pigments, and dioxazine pigments, or mixtures thereof can be used. As the solvent, toluene, xylene, ethyl acetate, butyl acetate, methyl alcohol, ethyl alcohol, isopropyl alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, water, or a mixture thereof can be used.
[0044] In addition, functional additives such as extender pigments, plasticizers, dispersants, surfactants, tackifiers, adhesion aids, drying agents, hardeners, hardening accelerators, and hardening retarders may be added to the base solid ink layer and the design layer 3 in order to impart various functions.
[0045] Here, the base solid ink layer and the design layer 3 can be formed by various printing methods such as gravure printing, offset printing, screen printing, electrostatic printing, inkjet printing, etc. In addition, since the base solid ink layer covers the entire surface of the base layer 2, it can also be formed by various coating methods such as roll coating, knife coating, microgravure coating, die coating, etc. These printing and coating methods may be selected separately depending on the layer to be formed, but it is more efficient to select the same method and process them all at once.
[0046] The thickness of the design layer 3 is preferably 3 μm or more and 20 μm or less. When the thickness of the design layer 3 is within this range, the printing can be made clear, the printing workability when producing the decorative sheet 1 is improved, and the production cost can be reduced.
[0047] <1.3>Transparent resin layer The resin material used as the main component of the transparent resin layer 4 is preferably made of an olefin-based resin, and in addition to polypropylene, polyethylene, polybutene, etc., α-olefins (for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-pent ... Examples of the polyolefin include a homopolymer or a copolymer of two or more of α-olefins (such as ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl methacrylate copolymer, ethylene-butyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, etc.) and a copolymer of ethylene or α-olefin with other monomers, such as ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, etc. Furthermore, when the surface strength of the decorative sheet 1 is to be improved, it is preferable to use a highly crystalline polypropylene.
[0048] In this specification, the term "main component" refers to 90% by mass or more of the target material, unless otherwise specified.
[0049] When a transparent resin layer 4 is provided, the thickness of the transparent resin layer 4 is preferably 50 μm or more and 100 μm or less. If it is less than 50 μm, the effect of improving the scratch resistance of the surface of the transparent resin layer 4 is low, and there is little point in providing the transparent resin layer 4. If the thickness of the transparent resin layer 4 exceeds 100 μm, the rigidity of the decorative sheet 1 is too high, and problems such as whitening and cracking may occur during bending.
[0050] However, when the surface protective layer 5 is provided on the transparent resin layer 4, the thickness of the transparent resin layer 4 may be less than 50 μm.
[0051] The resin composition constituting the transparent resin layer 4 may contain various functional additives such as a heat stabilizer, a light stabilizer, an ultraviolet absorber, an antiblocking agent, a catalyst trap, a colorant, a light scattering agent, and a gloss adjuster, if necessary. These various functional additives can be appropriately selected from well-known additives.
[0052] In addition, the adhesive used to bond the pattern layer 3 and the transparent resin layer 4 can be any material selected depending on the bonding method. Examples of bonding methods include lamination methods such as thermal lamination, extrusion lamination, and dry lamination, and the adhesive can be selected from acrylic, polyester, and polyurethane materials. In general, due to their cohesive strength, two-liquid curing urethane materials that utilize the reaction between isocyanate and polyol are desirable. There are no particular restrictions on the lamination method of the transparent resin layer 4, but methods that apply heat and pressure, extrusion lamination, and dry lamination are commonly used.
[0053] The transparent resin layer 4 may also be provided with an embossed pattern (embossed pattern 4a). Ink can be embedded in the embossed pattern 4a to further improve the design. The embossed pattern 4a can be provided by a method in which a sheet that has been laminated by various methods is embossed later by heat and pressure, or by a method in which a embossed pattern is provided on a cooling roll and embossed simultaneously with extrusion lamination.
[0054] Also, a method can be used in which the pattern layer 3 which has been embossed simultaneously with extrusion and the transparent resin layer 4 are bonded together by heat or dry lamination.
[0055] In addition, in order to improve the adhesion between the pattern layer 3 and the transparent resin layer 4, an adhesive resin layer 4b may be provided between the pattern layer 3 and the transparent resin layer 4. Specifically, when further lamination strength is required by the extrusion lamination method, an adhesive resin layer 4b may be provided between the transparent resin layer 4 and the adhesive. When the adhesive resin layer 4b is provided, lamination can be performed by co-extrusion of the transparent resin layer 4 and the adhesive resin layer 4b. The adhesive resin layer 4b can be an acid-modified resin such as polypropylene, polyethylene, or acrylic resin. The thickness of the adhesive resin layer 4b is desirably 2 μm or more for the purpose of improving the adhesive strength.
[0056] When the embossed pattern 4a is applied to the transparent resin layer 4, the uneven structure can be expressed by the cut level difference Rdc. The "cut level difference Rdc" is a surface property parameter defined in JIS B0601:2013. The cut level difference Rdc indicates the cut level difference of the roughness curve and expresses the steepness of the uneven shape. Here, the position of the highest peak of the roughness curve is the reference for the cut level c. Here, c(Rmr1) is the cut level when the load length ratio Rmr of the roughness curve is 10%, and c(Rmr2) is the cut level when the load length ratio Rmr of the roughness curve is 25%. The cut level difference Rdc (μm) of the roughness curve is the difference between the cut level c(Rmr1) and the cut level c(Rmr2). The Rdc of the transparent resin layer 4 is preferably 0.2 μm or more and 2.9 μm or less. If the Rdc is less than 0.2 μm, the effect of embedding the ink is weakened, and if it is more than 2.9 μm, when the surface protection layer 5 is formed on the transparent resin layer 4, the touch becomes rougher than the moist touch of the present invention, which is not preferable. The Rdc of the transparent resin layer 4 is preferably 0.2 μm or more and 1.0 μm or less.
[0057] <1.4>Surface protective layer As shown in FIG. 3, the surface protective layer 5 has a core portion 5A and a ridge portion 5B that protrudes in a ridge shape from one surface of the core portion 5A. This forms an uneven shape in the surface protective layer 5. Here, in the decorative sheet 1 according to this embodiment, the "ridge shape" refers to a shape that is elongated and raised, and is linearly connected in a plan view. The ridge portion 5B may be curved or linear in a plan view, but is preferably curved from the viewpoint of the fingerprint resistance of the decorative sheet 1. In this embodiment, the ridge portion 5B refers to, for example, the portion from the lowest part to the highest part of the uneven shape of the surface protective layer 5, and the core portion 5A refers to the portion of the surface protective layer 5 excluding the ridge portion 5B. The cross-sectional shape of the ridge portion 5B in the thickness direction of the surface protective layer 5 may be a sine wave shape. The sine wave shape here refers to a shape in which the line from the lowest position to the highest position of the ridge portion 5B can be expressed as a sine wave.
[0058] Fig. 3 is a cross-sectional view that typically shows a cross-section of ridge portion 5B of surface protective layer 5 (cross-section in the thickness direction of surface protective layer 5), and Fig. 4 is a planar photograph showing the configuration of the surface of surface protective layer 5. Here, Fig. 4 is a planar photograph obtained by a laser microscope (OLS-4000 manufactured by Olympus Corporation).
[0059] 4, the ridge portions 5B are elongated raised portions that are connected in a line in plan view. As will be described later, the ridge portions 5B are formed by irradiating the surface of the ionizing radiation curable resin with light of a specific wavelength, causing the cured film of the ionizing radiation curable resin to buckle.
[0060] The shape of the ridge portion 5B can be represented by the ratio RSm / Ra of the surface roughness index RSm (μm) in the horizontal direction (the planar direction of the surface protective layer 5, the left-right direction in FIG. 3) to the surface roughness index Ra (μm) in the vertical direction (the depth direction of the ridge portion 5B, the thickness direction of the transparent mold-imparting layer 5, the up-down direction in FIG. 3). The ratio RSm / Ra is preferably 10 or more and 300 or less. More preferably, RSm / Ra is 10 or more and 250 or less. When the value of the ratio RSm / Ra is small, the shape of the ridge portion 5B becomes finer, making it difficult to wipe off dirt and the contamination resistance tends to decrease. When the value of the ratio RSm / Ra is large, the interval between the ridge shapes becomes wider, so the gloss tends to increase. Here, the surface roughness indexes Ra and RSm are measured values when measured using a line roughness meter, and are measured values in accordance with JIS B0601.
[0061] The uneven structure of the surface protective layer 5 has a ratio Rdc / t (hereinafter simply referred to as "ratio Rdc / t") of the cutting level difference Rdc to the thickness t of the surface protective layer 5 of 0.15 to 0.44. The ratio Rdc / t is preferably 0.15 to 0.31, and more preferably 0.15 to 0.25.
[0062] As described above, the "cut level difference Rdc" is a surface quality parameter defined in JIS B0601:2013. The cut level difference Rdc indicates the cut level difference of the roughness curve and expresses the steepness of the uneven shape. Here, the position of the highest peak of the roughness curve is the reference for the cut level c. Also, here, c(Rmr1) is the cut level when the load length ratio Rmr of the roughness curve is 10%, and c(Rmr2) is the cut level when the load length ratio Rmr of the roughness curve is 25%. The cut level difference Rdc (μm) of the roughness curve is the difference between the cut level c(Rmr1) and the cut level c(Rmr2). The ratio Rdc / t is calculated by dividing the cut level difference Rdc by the thickness t of the surface protective layer 5, and the steepness of the uneven shape per unit thickness of the surface protective layer 5 can be expressed. In addition, the region of the surface of the surface protective layer corresponding to the portion where the load length ratio Rmr of the roughness curve is less than 10% is the region where the fingertip first comes into contact when the surface protective layer is pressed with the fingertip. The moist tactile sensation is not greatly influenced by the region of the surface of the surface protective layer where the fingertip first comes into contact when the pressure applied from the fingertip to the surface protective layer is extremely large. The moist tactile sensation is greatly influenced by the inclination of the region of the surface of the surface protective layer where the fingertip first comes into contact when the pressure applied from the fingertip to the surface protective layer is increased to a certain degree. This region corresponds to the region where the load length ratio Rmr of the roughness curve is in the range of 10% to 25%.
[0063] When the value of the ratio Rdc / t is 0.15 or more and 0.44 or less, the slope of the uneven shape is relatively gentle. In this case, when the surface of the decorative sheet is pressed with a finger and then slid over the surface, the resistance to the pressure caused by the contact between the finger and the surface is small, and the contact area between the finger and the convex surface gradually increases, resulting in a tactile sensation as if the surface of the decorative sheet is sticking to the finger. This tactile sensation can be associated with a "moist tactile sensation."
[0064] On the other hand, when the ratio Rdc / t is greater than 0.44, the slope of the uneven shape becomes steep. In this case, when a finger is pressed against the surface of the decorative sheet and then slid across the surface, the resistance to pressure caused by contact between the finger and the surface is large, and the presence of the unevenness is felt. This tactile sensation can be associated with a "rough tactile sensation."
[0065] Furthermore, when the ratio Rdc / t is smaller than 0.15, the slope of the uneven shape is quite gentle. In this case, when the surface of the decorative sheet is pressed with a finger and slid over the surface with the finger, the pressing resistance due to the contact between the finger and the surface is small, and the contact area between the finger and the convex surface is large from the start of the pressing motion, and the increase in this contact area accompanying the pressing motion is quite gentle. Therefore, in this case, the surface of the decorative sheet feels as if it is sticking to the finger, while the slope of the uneven shape is quite gentle, and a smooth feel is obtained compared to the above-mentioned "moist feel", and the overall impression of a smooth feel is stronger. This feel can be associated with a "smooth feel".
[0066] The thickness t of the surface protective layer 5 is 2 μm or more and 18 μm or less. The thickness t of the surface protective layer 5 is preferably 3 μm or more and 10 μm or less. When the surface protective layer 5 is made thicker, the value of the ratio Rdc / t tends to increase. In addition, when the surface protective layer 5 on the uneven transparent resin layer 4 is made thinner, the influence of the unevenness of the transparent resin layer 4 becomes larger, and the value of the ratio Rdc / t tends to increase. For this reason, when the surface protective layer 5 is too thick or too thin, it becomes difficult to achieve a "moist touch". Furthermore, when the surface protective layer 5 is made thin, it becomes difficult to achieve a low glossiness, and when it is made thicker, the processability decreases and whitening occurs when bending.
[0067] Here, the thickness of the surface protective layer 5 is the thickness of a layer having the same apparent area and volume as the surface protective layer 5 and a flat surface. The thickness of the surface protective layer 5 is determined, for example, by the following method. First, a cross section parallel to the thickness direction of the surface protective layer 5 and perpendicular to the length direction of the ridge portion 5B is imaged. Next, the dimension of the surface protective layer 5 in the width direction of the ridge portion 5B and the area of the cross section of the surface protective layer 5 are determined from this cross-sectional image. The thickness of the surface protective layer 5 is a value obtained by dividing this area by the above-mentioned dimension. In addition, the thickness of the surface protective layer 5 is obtained by observing the cross section with a scanning electron microscope and averaging 25 points. Specifically, the thickness of the surface protective layer 5 can be determined as described in the examples described later. In addition, when the coating liquid for the surface protective layer described later does not contain a solvent, the thickness of the coating film made of the coating liquid for the surface protective layer is equal to the thickness of the surface protective layer 5.
[0068] Here, the surface protective layer 5 can be formed by various printing methods such as gravure printing, offset printing, screen printing, electrostatic printing, inkjet printing, etc. In addition, since the surface protective layer 5 covers the entire surface of the surface side of the raw fabric layer 2, it can also be formed by various coating methods such as roll coating, knife coating, microgravure coating, die coating, etc. These printing methods or coating methods may be selected separately depending on the layer to be formed, or the same method may be selected and processed all at once.
[0069] The pattern layer 3 and the surface protective layer 5 may be synchronized from the viewpoint of design. In the case of synchronization, it is necessary to form the surface protective layer 5 all at once after forming the pattern layer 3, so it is preferable to use a gravure printing method. In addition, the gravure printing method is preferable because it allows relatively high speed processing and is advantageous in terms of cost. Here, synchronization means that 50% or more, preferably 70% or more, and most preferably 90% or more of the portion where the surface protective layer 5 is formed overlaps with the pattern portion of the pattern layer 3 in a planar view.
[0070] The thickness of the surface protective layer 5 can be adjusted by adjusting the amount of coating in the above-mentioned printing method and coating method. The amount of coating can be calculated from the mass difference between a base sheet (including a base layer) with the surface protective layer 5 formed and a base sheet without the surface protective layer 5 formed, in each printing method and coating method.
[0071] The main material of the surface protective layer 5 is preferably an ionizing radiation curable resin. The main material means that the material is contained in an amount of 60 parts by mass or more, more preferably 70 parts by mass or more, and most preferably 80 parts by mass or more, per 100 parts by mass of the surface protective layer 5. Here, the "ionizing radiation" refers to a charged particle beam such as an electron beam. The ionizing radiation curable resin is cured by irradiation with ionizing radiation. The ionizing radiation curable resin can also be cured by irradiation with ultraviolet light. The ionizing radiation curable resin used here is cured by irradiation with light having a wavelength of 200 nm or less, and has a large absorption coefficient for this light. As the ionizing radiation curable resin constituting the surface protective layer 5, known materials such as various monomers and commercially available oligomers can be used, and for example, (meth)acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, and epoxy resins can be used. The ionizing radiation curable resin may be either an aqueous resin or a non-aqueous (organic solvent-based) resin, and may be used alone or in combination of multiple types.
[0072] The main component of the ionizing radiation curable resin is preferably an acrylate. Here, the main component of the ionizing radiation curable resin means a component that accounts for 60 mass% or more of the ionizing radiation curable resin. The ionizing radiation curable resin preferably contains 70 mass parts or more of acrylate, more preferably 80 mass parts or more.
[0073] The acrylate is preferably a bifunctional or higher acrylate, and more preferably a trifunctional or higher acrylate. In order to obtain a surface protective layer 5 having excellent scratch resistance, the acrylate is preferably a trifunctional or higher acrylate. There is no upper limit to the number of functional groups of the acrylate, but according to one example, it is 6-functional or lower.
[0074] The acrylate preferably contains a repeating structure. The repeating structure is, for example, any one of an ethylene oxide (EO) structure, a propylene oxide (PO) structure, and an ε-caprolactone (CL) structure. The repeating structure is preferably ethylene oxide or propylene oxide. In the acrylate, the repeating structure may be present between an acryloyl group and a methylol group in a ring-opened state.
[0075] The number of repetitions of the repeating structure is preferably 3 or more. When an acrylate having a large number of repetitions is used, the cured film is likely to expand in the in-plane direction in the first irradiation step described below, and therefore wrinkles corresponding to the ridges 5B are likely to appear on the coating film surface. In addition, when an acrylate having a large number of repetitions is used, the ratio Rdc / t tends to increase. However, when the number of repetitions is increased, the crosslink density decreases, and the scratch resistance of the surface protective layer decreases.
[0076] In a preferred embodiment, the ionizing radiation curable resin is a trifunctional acrylate containing a repeating structure. For example, EO-modified, PO-modified or CL-modified trimethylolpropane triacrylate, glycerin triacrylate, isocyanurate triacrylate, pentaerythritol triacrylate, etc. can be used as the trifunctional acrylate containing a repeating structure. When the gravure printing method is used as the coating method, the optimum viscosity range of the ionizing radiation curable resin is 10 to 500 mPa·s. Therefore, it is preferable to use trimethylolpropane triacrylate or glycerin triacrylate as the trifunctional acrylate resin, since it is possible to keep the viscosity within the optimum range. Resins having a skeleton that causes hydrogen bonds or π-π stacking often have a high viscosity of 500 mPa·s or more, which is not preferable. In addition, organic solvents or low-viscosity bifunctional acrylate resins can be added to adjust the viscosity. However, it is preferable not to use organic solvents from the viewpoint of environmental load. The bifunctional acrylate resin is not preferred because the scratch resistance decreases when the amount of the bifunctional acrylate resin is large, and therefore the amount of the bifunctional acrylate resin added is preferably within a range of 10% by mass to 30% by mass of the content (mass) of the trifunctional acrylate resin.
[0077] In a trifunctional acrylate containing a repeating structure, the number of repeats of the repeating structure is preferably 3 or more, more preferably 3 to 30, and even more preferably 3 to 20. If the number of repeats is small, the cured film of the ionizing radiation curable resin constituting the surface protective layer 5 is unlikely to swell in the in-plane direction when irradiated with vacuum ultraviolet light (VUV light), and therefore wrinkles are not sufficiently formed, making it difficult for the surface protective layer 5 to have a low gloss. If the number of repeats is large, the crosslinking density decreases, and the scratch resistance of the surface protective layer 5 tends to decrease.
[0078] In another preferred embodiment, the ionizing radiation curable resin is a tetrafunctional acrylate containing a repeating structure. For example, EO-modified, PO-modified or CL-modified pentaerythritol tetraacrylate can be used as the tetrafunctional acrylate containing a repeating structure. In the tetrafunctional acrylate containing a repeating structure, the repeating number of the repeating structure is preferably 12 or more, more preferably 12 to 50, even more preferably 20 to 50, and even more preferably 20 to 35. If the repeating number is small, when irradiated with VUV light, the cured film of the ionizing radiation curable resin constituting the surface protective layer 5 is difficult to swell in the in-plane direction, and therefore wrinkles are not sufficiently formed, so that the surface protective layer 5 is difficult to have a low gloss. If the repeating number is large, the crosslinking density decreases, and the scratch resistance of the surface protective layer 5 tends to decrease.
[0079] The number of repetitions of the repeating structure can be analyzed by using MALDI-TOF-MS. Ionizing radiation curable resins may have a molecular weight distribution. When there is a molecular weight distribution, the number of repetitions is the number of repetitions corresponding to the molecular weight having the strongest peak in the mass spectrum of MALDI-TOF-MS. The number of repetitions of the repeating structure can be determined by using the ratio I 1095 / I 1725 may be calculated and determined based on such a ratio.
[0080] The absorption spectrum obtained by Fourier infrared spectroscopy of the surface protective layer 5 is 1085 to 1105 cm -1 Maximum value in the wavenumber range of I 1095 and 1715 to 1735 cm -1 Maximum value in the wavenumber range of I 1725 Comparison with I 1095 / I 1725 is 0.65 or more. 1095 / I 1725If the value of I is less than 0.65, the number of repetitions is small, so that when irradiated with VUV light, the cured film of the ionizing radiation curable resin constituting the surface protective layer 5 is unlikely to swell in the in-plane direction, and therefore wrinkles are not sufficiently formed, and the surface protective layer 5 does not have a low gloss. 1095 / I 1725 The value of is preferably 0.7 or more, and more preferably 0.85 or more.
[0081] Ratio I 1095 / I 1725 If the value of I is too large, the crosslink density decreases and the scratch resistance of the surface protective layer 5 decreases. 1095 / I 1725 It is desirable that the value of I is 3.5 or less. 1095 / I 1725 The value is more preferably 2.2 or less, and further preferably 1.3 or less.
[0082] Here, the above-mentioned Fourier type infrared spectrometry will be described. Infrared light with wavelengths in the range of 2.5 to 25 μm can change the vibrational and rotational states of molecules. The energy required to change these vibrational and rotational states varies depending on the structure of the molecule. Infrared spectroscopy is a measurement method that utilizes this to obtain information about the chemical structure and state of a substance.
[0083] In Fourier infrared spectrometry, for example, measurement is performed as follows. First, light from a light source is obliquely incident on a semi-transparent mirror and split into two beams of transmitted light and reflected light. The beam that has passed through the semi-transparent mirror is reflected by a fixed mirror and is obliquely re-incident on the semi-transparent mirror. The beam reflected by the semi-transparent mirror is reflected by a movable mirror and is obliquely re-incident on the semi-transparent mirror. The beam reflected by the semi-transparent mirror out of the light reflected from the fixed mirror and the beam reflected by the movable mirror that has passed through the semi-transparent mirror are combined to generate an interference wave. While changing the distance from the semi-transparent mirror to the movable mirror, this interference wave is irradiated onto a sample, and the intensity of the light that has passed through the sample is measured. The intensity data obtained in this way is separated into the intensities of each wave number component by calculation (Fourier transform) to obtain a transmittance spectrum.
[0084] In the Fourier infrared spectrometry used here, instead of measuring the transmitted light intensity in the above-mentioned Fourier infrared spectrometry, the reflected light intensity is measured by the following attenuated total reflection method (ATR method).
[0085] In Fourier transform infrared spectroscopy using the ATR method, instead of directly incident on the sample, the interference wave is incident on a measurement prism that is in contact with the surface of the sample. The interference wave is incident on the measurement prism so that it is totally reflected at the interface between the prism and the sample. In this way, evanescent waves seep into the area of the sample near the interface, and light of a specific wave number component is absorbed by molecules in this area. Then, in Fourier transform infrared spectroscopy using the ATR method, instead of measuring the intensity of transmitted light, the intensity of reflected light is measured. The intensity data obtained in this way is then separated by calculation into the intensities of each wave number component (Fourier transform) to obtain the ATR spectrum.
[0086] The penetration depth (depth of penetration) of the evanescent wave increases as the wavelength becomes longer. Therefore, the baseline of the ATR spectrum, in which the horizontal axis is the wavelength and the vertical axis is the reflected light intensity (or reflectance), slopes downward to the right. The penetration depth of the evanescent wave is also affected by the angle of incidence of the interference wave on the interface and the refractive index of the prism and the sample. Therefore, the ATR spectrum is corrected by the reciprocal of the wavelength, etc. By performing such correction, a spectrum having the same peak intensity ratio as the transmittance spectrum can be obtained. Then, by converting this spectrum, an absorption spectrum can be obtained, in which the horizontal axis is the wave number and the vertical axis is the absorbance.
[0087] The penetration depth of the evanescent wave is small, and can be adjusted by the angle of incidence of the interference wave and the refractive index of the prism. Therefore, Fourier transform infrared spectroscopy using the ATR method can prevent the underlying layer from becoming noise, even if the object to be measured is a thin layer. In addition, Fourier transform infrared spectroscopy using the ATR method allows non-destructive measurement as long as the object to be measured is exposed on the surface of the sample.
[0088] As described above, the absorption spectrum obtained by Fourier infrared spectroscopy of the surface protective layer 5 has a ratio I 1095 / I 1725 is within the specified range. 1085 to 1105 cm -1 Maximum value in the wavenumber range of I 1095 is a value related to the number of ether bonds contained in the surface protective layer 5. -1 Maximum value in the wavenumber range of I 1725 is a value related to the number of ester bonds. Therefore, the ratio I 1095 / I 1725 corresponds to the ratio of the number of ether bonds to the number of functional groups of the acrylate contained in the ionizing radioactive resin of the coating liquid for the surface protective layer described below.
[0089] The surface protection layer 5 may contain particles. By adding particles of an optimal particle size and an optimal content, a uniform surface can be formed. As the particles, for example, organic materials such as polyethylene (PE) wax, polypropylene (PP) wax, and resin beads, or inorganic materials such as silica, glass, alumina, titania, zirconia, calcium carbonate, and barium sulfate can be used. It is desirable that the average particle size (D50) of the particles is 3 μm or more. The average particle size (D50) of the particles is preferably 3 μm or more and 11 μm or less, and more preferably 4 μm or more and 10 μm or less.
[0090] When the surface protective layer 5 contains particles, wrinkles can be more uniformly generated on the coating surface in the first irradiation step described below. When the average particle size (D50) of the particles increases, the ratio Rdc / t tends to decrease. For this reason, if the average particle size (D50) is too small or too large, it becomes difficult to achieve a "moist tactile feel." In addition, when large particles are used, the particles are likely to fall off from the surface protective layer 5, making it difficult to achieve high scratch resistance. When the particles are small, the effect of generating wrinkles uniformly is small.
[0091] Here, the "average particle size (D50)" is the median size (D50) measured by a laser diffraction / scattering type particle size distribution measuring device. When the coating liquid for the surface protective layer contains particles, the surface protective layer 5 obtained from this coating liquid also contains particles. The average particle size of the particles contained in the surface protective layer 5 can be determined by observing the cross section of the layer, measuring the particle sizes of a plurality of particles, and averaging the measured values. The value thus obtained is substantially the same as the median size (D50) measured by a laser diffraction / scattering type particle size distribution measuring device. Therefore, the above-mentioned range of the average particle size can also be read as the range of the average particle size of the particles contained in the surface protective layer 5.
[0092] The particles are preferably contained in the surface protection layer 5 in an amount of 3 to 11 parts by mass per 100 parts by mass of the ionizing radiation curable resin. The amount of the particles added is more preferably 4 to 10 parts by mass per 100 parts by mass of the resin. Note that "100 parts by mass of resin" refers to the parts by mass of the solid content of the resin.
[0093] When the amount of particles added is within the above range, the effect of generating wrinkles uniformly is particularly large. When the amount of particles added is large, the value of the ratio Rdc / t tends to decrease. Therefore, when the amount of particles added is too small or too large, it becomes difficult to achieve a "moist touch". In addition, when the amount of particles added is large, the particles are likely to fall off from the surface protective layer 5, and it may be difficult to achieve high scratch resistance. When the amount of particles added is small, the effect of generating wrinkles uniformly is small.
[0094] When the entire surface protective layer 5 is cured by UV light, it is necessary to add a photopolymerization initiator to the surface protective layer 5. The photopolymerization initiator is not particularly limited, but examples thereof include benzaphenone-based, acetophenone-based, benzoin ether-based, and thioxanthone-based initiators.
[0095] The surface protective layer 5 may further contain additives such as antibacterial agents and antifungal agents to impart required functions. In addition, as other additives, it may further contain ultraviolet absorbers and light stabilizers as necessary. In general, ultraviolet absorbers such as benzotriazoles, benzoates, benzophenones, and triazines, and light stabilizers such as hindered amines are added in any combination.
[0096] Examples of the hindered amine light stabilizer that can be used include bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate (a representative example is BASF's product name "Tinuvin 144"), BASF's product name "Tinuvin 123", and a reaction product of decanedioic acid bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) ester (1,1-dimethylethyl hydroperoxide) and octane.
[0097] When the hindered amine light stabilizer is added to the surface protective layer 5, it is preferable to add it in the range of 0.05 parts by mass to 5 parts by mass to 100 parts by mass of the ionizing radiation curable resin. The amount of the hindered amine light stabilizer added is more preferably in the range of 0.2 parts by mass to 3 parts by mass. If the amount of the hindered amine light stabilizer added is less than 0.05 parts by mass, the effect of the stability of the resin against ultraviolet rays may be low. On the other hand, if it is more than 5 parts by mass, the possibility of bleeding out increases. In addition, the surface protective layer 5 can be formed by irradiating light of 200 nm or less to cure and shrink the vicinity of the surface to form a fine uneven shape, but in this case, if the hindered amine light stabilizer is contained in an amount of more than 3 parts by mass, the curing of the vicinity of the surface may be inhibited. In order to achieve both low gloss and weather resistance, it is desirable to contain the hindered amine light stabilizer in the range of 3 parts by mass or less.
[0098] The glossiness of the surface protective layer 5 is preferably less than 10.0. The glossiness of the surface protective layer 5 is more preferably 5.0 or less. Here, the "glossiness" is a value measured at an incidence angle of 60 degrees using a glossmeter conforming to JIS Z8741:1997.
[0099] <1.5> Primer layer The primer layer 6 can be made of the same material as the pattern layer 3. Considering that the primer layer 6 is applied to the back surface of the decorative sheet 1 and is wound in a web form, inorganic fillers such as silica, alumina, magnesia, titanium oxide, barium sulfate, etc. may be added to avoid blocking and improve adhesion with the adhesive. The coating thickness of the primer layer 6 is preferably 0.1 μm or more and 3.0 μm or less, since the purpose is to ensure adhesion with the substrate B. The primer layer 6 is necessary when the base layer 2 has an inactive surface such as an olefin-based material, but is not particularly necessary when the surface is active.
[0100] <2> Manufacturing method of decorative sheet The decorative sheet 1 is produced, for example, by the following method. For the sake of brevity, explanations regarding the design layer 3, transparent resin layer 4, adhesive resin layer 4b, and primer layer 6 are omitted here.
[0101] First, a coating film made of a coating liquid for a surface protective layer is formed on one surface of the raw film layer 2. As described in the section <1.4> Surface protective layer, the coating liquid for a surface protective layer contains an ionizing radiation curable resin, and, if necessary, particles and additives. The coating film made of the coating liquid for a surface protective layer can be formed, for example, by printing.
[0102] After forming a coating film made of the coating liquid for surface protection layer, a first irradiation step is carried out. In the first irradiation step, the coating film is irradiated with light having a wavelength of 200 nm or less (hereinafter referred to as the first radiation). The ionizing radiation curable resin contained in the coating liquid for surface protection layer has a large absorption coefficient for the first radiation. Therefore, the first radiation incident on the coating film can only reach a position several tens to several hundreds of nm away from the outermost surface. Therefore, in the first irradiation step, a crosslinking reaction proceeds in the surface region of the coating film to form an extremely thin cured film, while in other regions, the crosslinking reaction does not proceed and the coating film remains uncured.
[0103] The coating film after the first irradiation step has wrinkles on its surface corresponding to the ridge portions 5 B. The present inventors consider the reason why wrinkles are formed on the coating film surface by the first irradiation step to be as follows.
[0104] As described above, the first radiation can only reach a position that is several tens to several hundreds of nm away from the outermost surface of the coating film. In other words, the crosslinking reaction of the ionizing radiation curable resin occurs only on the surface of the coating film, and the area that is more than several tens to several hundreds of nm away from the outermost surface is uncured and contains highly fluid molecules. Such highly fluid molecules swell the cured film, thereby increasing the volume of the cured film. The cured film buckles in response to the in-plane compressive stress caused by the increase in volume in the in-plane direction, resulting in wrinkles on the surface of the coating film.
[0105] The first radiation can be extracted from excimer VUV light. Excimer VUV light can be produced from a lamp that uses a rare gas or a rare gas halide compound. When high-energy electrons are provided from the outside to a lamp that contains a rare gas or a rare gas halide compound gas, a large number of discharge plasmas (dielectric barrier discharges) are generated. This plasma discharge excites the atoms of the discharge gas (rare gas), which momentarily enters an excimer state. When returning from this excimer state to the ground state, light is emitted in a wavelength range specific to that excimer.
[0106] The gas used in the excimer lamp may be any conventional gas that emits light of 200 nm or less. The gas may be a rare gas such as Xe, Ar, or Kr, or a mixture of a rare gas such as ArBr or ArF and a halogen gas. The central wavelength of the excimer lamp varies depending on the gas, and may be, for example, about 172 nm (Xe), about 126 nm (Ar), about 146 nm (Kr), about 165 nm (ArBr), or about 193 nm (ArF).
[0107] Considering the magnitude of photon energy and the difference between the wavelength and the bond energy of organic matter, it is preferable to use a xenon lamp that emits excimer light with a central wavelength of 172 nm as the light source. Also, considering the cost of maintaining the equipment and the availability of materials, it is preferable to use a xenon lamp as the light source.
[0108] The first irradiation step is carried out in an atmosphere with a low oxygen concentration. Oxygen has a large absorption coefficient for light of 200 nm or less. Therefore, the first irradiation step is preferably carried out in, for example, a nitrogen gas atmosphere. The oxygen concentration in the gas phase in the first irradiation step, i.e., the residual oxygen concentration in the reaction atmosphere, is preferably 2000 ppm or less, more preferably 1000 ppm or less.
[0109] In addition, oxygen in the atmosphere inhibits radical polymerization. Therefore, the residual oxygen concentration in the reaction atmosphere affects the formation of wrinkles on the coating surface. Therefore, changing the residual oxygen concentration in the reaction atmosphere can also change the surface properties of the surface protective layer 5.
[0110] The cumulative light intensity of the first radiation is 0.5 mJ / cm 2 More than 200mJ / cm 2 It is preferable that the concentration is 1 mJ / cm or less. 2 More than 100mJ / cm 2 More preferably, it is 3 mJ / cm or less. 2 More than 50mJ / cm 2 More preferably, it is 5 mJ / cm or less. 2 More than 30mJ / cm 2It is most preferable to set the integrated light amount to the following value. If the integrated light amount is small, the expansion of the cured film in the in-plane direction is small. If the integrated light amount is large, the surface condition of the coating film is deteriorated.
[0111] After the first irradiation step is completed, the second irradiation step is carried out. In the second irradiation step, the coating film is irradiated with a second radiation to cure the entire coating film. As a result, the surface protective layer 5 is obtained.
[0112] The second radiation is ionizing radiation such as an electron beam, or ultraviolet radiation having a longer wavelength than the first radiation. When ultraviolet radiation is used as the second radiation, the ultraviolet radiation has a wavelength at which the ionizing radiation curable resin exhibits a small absorption coefficient.
[0113] The cumulative light intensity of the second radiation is 10 mJ / cm 2 More than 500mJ / cm 2 It is preferable to set the dose to 50 mJ / cm or less. 2 More than 400mJ / cm 2 More preferably, it is 100 mJ / cm or less. 2 More than 300mJ / cm 2 It is even more preferable that: The decorative sheet 1 can be manufactured by, for example, the above-mentioned method. The decorative sheet 1 may also be manufactured by other methods. For example, a plate may be formed using the method described above for the surface protective layer 5, and the surface protective layer 5 having a concave-convex structure on its surface may be formed by transfer using this plate.
[0114] <3> Actions and other The decorative sheet 1 described with reference to Figures 1 to 4 has a surface protective layer 5 with the above-mentioned surface properties. Such a decorative sheet 1 gives the user a moist tactile sensation when the user slides a finger over the surface while pressing the surface of the surface protective layer 5 with the skin, for example, when the user slides a finger over the surface while pressing the surface of the surface protective layer 5 with the finger. That is, since the slope of the uneven shape on the surface of the surface protective layer 5 of this decorative sheet 1 is relatively gentle, when the user touches the surface in the above manner, the contact area between the finger and the convex surface can be gradually increased while keeping the pressing resistance caused by the contact between the finger and the surface small. This gives the user a tactile sensation as if the surface of the decorative sheet is sticking to the finger.
[0115] The moist tactile sensation can give a sense of comfort and warmth to a person who touches the decorative sheet 1. Furthermore, the moist tactile sensation can impart a sense of luxury to the decorative sheet 1. Therefore, the decorative sheet 1 that gives the user a moist tactile sensation is suitable for use in applications where the user's skin frequently comes into contact with the sheet or where the user's skin comes into contact with the sheet for a long period of time, such as table tops, chair armrests, handrails on stairs or in corridors, etc.
[0116] Since the surface protective layer 5 of the decorative sheet 1 has the above-mentioned surface properties, it can achieve a low gloss even without containing a gloss regulator (matt additive). The gloss regulator reduces the oil repellency of the layer formed from the resin material, so the surface protective layer 5 containing the gloss regulator is prone to fingerprints. The surface protective layer 5 not containing the gloss regulator is less likely to absorb oil, so fingerprints are less likely to be attached. In addition, the surface protective layer 5 with excellent oil repellency is less likely to cause oil stains or adsorption of contaminants. Furthermore, the surface protective layer 5 not containing the gloss regulator does not lose the particles of the gloss regulator when its surface is scratched, so the decorative sheet 1 containing such a surface protective layer 5 is less likely to cause gloss changes or scratches. The decorative sheet 1 is excellent in fingerprint resistance, contamination resistance, and scratch resistance, as well as weather resistance and processability.
[0117] The reason why the surface protective layer 5 having the above-mentioned surface properties can be obtained by the above-mentioned method is as follows.
[0118] Oxygen in the gas phase not only absorbs short-wavelength ultraviolet rays, but also inhibits radical polymerization. The effect of oxygen in the gas phase on radical polymerization is greatest in the portion of the coating film made of ionizing radiation curable resin adjacent to the gas phase, and decreases as the distance from the coating film surface increases. Therefore, by changing the oxygen concentration in the gas phase in the first irradiation step, the relationship between the distance from the coating film surface and the progress of the crosslinking reaction can be changed.
[0119] When this relationship changes, the thickness of the cured film formed on the surface of the coating film by the first irradiation step and the degree of expansion of the cured film in the in-plane direction according to the progress of the crosslinking reaction change. The thickness of the cured film and the degree of expansion of the cured film in the in-plane direction are also affected by the integrated light amount in the first irradiation step. The thickness of the cured film and the degree of expansion of the cured film in the in-plane direction also affect the surface properties of the surface protective layer. Furthermore, the particle size and amount of particles added in the coating film, as well as the thickness of the coating film, also affect the formation of wrinkles.
[0120] Therefore, for example, by appropriately setting the composition of the ionizing radiation curable resin, the thickness of the coating film, the oxygen concentration in the gas phase in the first irradiation step, and the integrated light amount in the first irradiation step, it is possible to obtain a surface protection layer having the desired surface properties. EXAMPLES
[0121] In the following, examples of the present invention are described.
[0122] <Example 1> An olefin film (manufactured by RIKEN TECHNOS CORPORATION) having a thickness of 55 μm was used as the original layer 2, one side of the original layer 2 was subjected to corona treatment, and the other side was subjected to pattern printing to form the pattern layer 3. The pattern layer 3 was formed using a two-liquid urethane ink (V180; manufactured by Toyo Ink Co., Ltd.) to which 0.5 parts by mass of a hindered amine-based light stabilizer (Chimasorb 944; manufactured by BASF) was added relative to the binder resin content of the ink. The cut level difference Rdc of the surface of the pattern layer 3 was 0.4 μm. The cut level difference Rdc was measured using a surface roughness meter (manufactured by Mitutoyo Corporation, SJ-310) under the measurement conditions of a cutoff value λc of 2.5 mm, a cutoff value λs of 8 μm, and an evaluation length of 12.5 mm. Measurements were performed at any five points along a direction perpendicular to the film formation direction, and the average value was taken as the measured value.
[0123] Next, a primer layer 6 was formed on the back surface of the base layer 2. The primer layer 6 was formed by printing with the same two-component urethane ink as that for the design layer 3.
[0124] Next, a coating liquid for a surface protective layer was applied onto the design layer 3. The thickness of the coating liquid for a surface protective layer was 5 μm. The coating liquid for a surface protective layer was made by blending the following ionizing radiation curable resin with the following additives (particles, photopolymerization initiator). ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 15 moles added) Product name: SR9035 (Sartomer) Blend: 100 parts by mass ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 5 parts by mass Photopolymerization initiator Product name: Omnirad184 (IGM Resins) Blend: 3 parts by mass.
[0125] Thereafter, the first irradiation step was carried out. Specifically, under atmospheric pressure and in a nitrogen gas atmosphere with an oxygen concentration of 100 ppm, ultraviolet rays having a wavelength of 172 nm were irradiated to the surface of the coating film made of the coating liquid for surface protective layer with an integrated light amount of 30 mJ / cm using a Xe excimer lamp. 2 This caused wrinkles to form on the surface of the coating film.
[0126] Subsequently, the second irradiation step was carried out. Specifically, the coating film was irradiated with 200 mJ / cm using a high-pressure mercury lamp. 2 The whole was cured by irradiating it with ultraviolet light so as to form a surface protective layer 5. In this manner, a decorative sheet 1 having a total thickness of 60 μm was obtained.
[0127] <Example 2> A decorative sheet having a total thickness of 60 μm was obtained in the same manner as in Example 1, except that the ionizing radiation curable resin in Example 1 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 15 moles added) Product name: SR9035 (Sartomer) Blend: 75 parts by mass Type: Dipentaerythritol hexaacrylate Blend: 25 parts by mass.
[0128] <Example 3> A decorative sheet having a total thickness of 60 μm was obtained in the same manner as in Example 1, except that the ionizing radiation curable resin in Example 1 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 15 moles added) Product name: SR9035 (Sartomer) Blend: 50 parts by mass Type: Dipentaerythritol hexaacrylate Blend: 50 parts by mass.
[0129] <Comparative Example 1> A decorative sheet having a total thickness of 60 μm was obtained in the same manner as in Example 1, except that the ionizing radiation curable resin in Example 1 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 15 moles added) Product name: SR9035 (Sartomer) Blend: 25 parts by mass Type: Dipentaerythritol hexaacrylate Blend: 75 parts by mass.
[0130] <Comparative Example 2> A decorative sheet having a total thickness of 60 μm was obtained in the same manner as in Example 1, except that the ionizing radiation curable resin in Example 1 was replaced with the following. ·Ionizing radiation curable resin Type: Dipentaerythritol hexaacrylate Blend: 100 parts by mass.
[0131] <Example 4> As in Example 1, a sheet consisting of a primer layer 6, a raw fabric layer 2, and a pattern layer 3 was produced. Next, a mixture of 100 parts by mass of crystalline polypropylene resin (pentad fraction 97.8%, molecular weight distribution 2.3, MFR 18g / 10min), 0.5 parts by mass of a hindered amine-based light stabilizer (BASF's "Kimassorb 944"), and 0.5 parts by mass of a benzotriazole-based ultraviolet absorber (BASF's "Tinuvin 328") was co-extruded with a polyethylene-based easy-adhesive resin using a melt extruder to form a transparent resin layer 4 having a thickness of 60 μm and an adhesive resin layer 4b having a thickness of 10 μm. Next, a dry lamination adhesive (Takelac A540; Mitsui Chemicals, Inc.; coating amount 2 g / m) was applied to the surface of the pattern layer 3. 2 ) was applied to the sheet. The pattern layer 3 surface of the sheet to which the adhesive was applied was then bonded to the transparent resin layer 4 by extrusion lamination via the adhesive resin layer 4b formed. Furthermore, an embossed pattern 4a was applied to the surface of the sheet formed by bonding, facing the transparent resin layer 4, by pressing using a die roll for embossing. As a result, the cut level difference Rdc of the surface of the transparent resin layer 4 was 0.5 μm.
[0132] Next, a coating liquid for a surface protective layer was applied onto the transparent resin layer 4. The layer thickness of the coating liquid for a surface protective layer was set to 5 μm. The coating liquid for a surface protective layer was prepared by blending the following ionizing radiation curable resin with the following additives (particles, photopolymerization initiator). ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 15 moles added) Product name: SR9035 (Sartomer) Blend: 100 parts by mass ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 5 parts by mass Photopolymerization initiator Product name: Omnirad184 (IGM Resins) Blend: 3 parts by mass.
[0133] Thereafter, the first irradiation step was carried out. Specifically, under atmospheric pressure and in a nitrogen gas atmosphere with an oxygen concentration of 100 ppm, ultraviolet rays having a wavelength of 172 nm were irradiated to the surface of the coating film made of the coating liquid for surface protective layer with an integrated light amount of 30 mJ / cm using a Xe excimer lamp. 2 This caused wrinkles to form on the surface of the coating film.
[0134] Subsequently, the second irradiation step was carried out. Specifically, the coating film was irradiated with 200 mJ / cm using a high-pressure mercury lamp. 2 The whole was cured by irradiating it with ultraviolet light so as to form a surface protective layer 5. In this manner, a decorative sheet having a total thickness of 130 μm was obtained.
[0135] <Example 5> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that when the embossed pattern 4a was imparted to the transparent resin layer 4 of Example 4, a mold roll different from that used in Example 4 was used for pressing to change the cut level difference Rdc of the surface of the transparent resin layer 4. In Example 5, the cut level difference Rdc of the surface of the transparent resin layer 4 was 2.6 μm.
[0136] <Example 6> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that when the embossed pattern 4a was imparted to the transparent resin layer 4 of Example 4, a mold roll different from that used in Example 4 was used for pressing to change the cut level difference Rdc of the surface of the transparent resin layer 4. In Example 6, the cut level difference Rdc of the surface of the transparent resin layer 4 was 3.2 μm.
[0137] <Comparative Example 3> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that when the embossed pattern 4a was imparted to the transparent resin layer 4 of Example 4, a mold roll different from that used in Example 4 was used for pressing to change the cut level difference Rdc of the surface of the transparent resin layer 4. In Comparative Example 3, the cut level difference Rdc of the surface of the transparent resin layer 4 was 3.5 μm.
[0138] <Comparative Example 4> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the first irradiation step of Example 4 was not carried out and the second irradiation step was carried out.
[0139] <Example 7> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 20 moles added) Product name: NK Ester AT-20E (manufactured by Shin-Nakamura Chemical Co., Ltd.) Blend: 100 parts by mass.
[0140] <Example 8> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (9 moles of EO added) Product name: SR502 (Sartomer) Blend: 100 parts by mass.
[0141] <Example 9> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 6 moles added) Product name: Miramer M3160 (Miwon) Blend: 100 parts by mass.
[0142] <Example 10> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane EO modified triacrylate (EO 3 moles added) Product name: Miramer M3130 (Miwon) Blend: 100 parts by mass.
[0143] <Comparative Example 5> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane triacrylate Product name: NK Ester A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd.) Blend: 100 parts by mass.
[0144] <Example 11> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles of Example 4 (product name: Sylysia 250N) were not added.
[0145] <Comparative Example 6> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 5, except that the particles of Example 5 (product name: Sylysia 250N) were not added.
[0146] <Comparative Example 7> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 6, except that the particles of Example 6 (product name: Sylysia 250N) were not added.
[0147] <Comparative Example 8> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 7, except that the particles of Example 7 (product name: Sylysia 250N) were not added.
[0148] <Example 12> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 8, except that the particles of Example 8 (product name: Sylysia 250N) were not added.
[0149] <Example 13> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 9, except that the particles of Example 9 (product name: Sylysia 250N) were not added.
[0150] <Example 14> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 10, except that the particles of Example 10 (product name: Sylysia 250N) were not added.
[0151] <Comparative Example 9> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the layer thickness of the coating liquid for surface protective layer in Example 4 was changed to 1 μm.
[0152] <Example 15> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the layer thickness of the coating liquid for surface protective layer in Example 4 was changed to 2 μm.
[0153] <Example 16> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the layer thickness of the coating liquid for surface protective layer in Example 4 was changed to 10 μm.
[0154] <Example 17> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the layer thickness of the coating liquid for surface protective layer in Example 4 was changed to 18 μm.
[0155] <Comparative Example 10> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the layer thickness of the coating liquid for surface protective layer in Example 4 was changed to 20 μm.
[0156] <Example 18> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles in Example 4 were changed as follows. ·particle Product name: Silica 310P (manufactured by Fuji Silysia Chemical) Particle size: 2μm.
[0157] <Example 19> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles in Example 4 were changed as follows. ·particle Product name: Silica 420 (manufactured by Fuji Silysia Chemical) Particle size: 3μm.
[0158] <Example 20> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles in Example 4 were changed as follows. ·particle Product name: Silica 450 (manufactured by Fuji Silysia Chemical) Particle size: 8μm.
[0159] <Example 21> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles in Example 4 were changed as follows. ·particle Product name: Silica 780 (manufactured by Fuji Silysia Chemical) Particle size: 11μm.
[0160] <Example 22> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the particles in Example 4 were changed as follows. ·particle Product name: sicastar43-00-154 (manufactured by Corefront) Particle size: 14μm.
[0161] <Example 23> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the blending amount of the particles in Example 4 was changed as follows. ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 2 parts by mass.
[0162] <Example 24> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the blending amount of the particles in Example 4 was changed as follows. ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 3 parts by mass.
[0163] <Example 25> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the blending amount of the particles in Example 4 was changed as follows. ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 11 parts by mass.
[0164] <Example 26> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the blending amount of the particles in Example 4 was changed as follows. ·particle Product name: Silica 250N (manufactured by Fuji Silysia Chemical) Particle size: 5μm Blend: 12 parts by mass.
[0165] <Example 27> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Ethoxylated pentaerythritol tetraacrylate (20 moles of EO added).
[0166] <Example 28> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Ethoxylated pentaerythritol tetraacrylate (35 moles of EO added) Product name: NK Ester ATM-35E (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0167] <Comparative Example 11> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Ethylene glycol diacrylate (9 moles of EO) Product name: Light Acrylate 9EG-A (manufactured by Kyoeisha Chemical Co., Ltd.).
[0168] <Comparative Example 12> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Ethoxylated dipentaerythritol hexaacrylate (12 moles of EO added) Product name: NK Ester A-DPH-12E (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0169] <Comparative Example 13> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Pentaerythritol tetraacrylate Product name: NK Ester A-TMMT (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0170] <Example 29> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Trimethylolpropane PO modified triacrylate (6 moles of PO added) Product name: NK Ester A-TMPT-6PO (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0171] <Example 30> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the ionizing radiation curable resin in Example 4 was replaced with the following. ·Ionizing radiation curable resin Type: Caprolactone-modified tris-(2-acryloxyethyl) isocyanurate (3 moles of caprolactone added) Product name: NK Ester A-9300-3CL (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0172] <Example 31> No photopolymerization initiator was added to the ionizing radiation curable resin of Example 4. In the second irradiation step, the coating film was irradiated with ionizing radiation and cured entirely to form a surface protective layer 5. All other steps were the same as in Example 4 to obtain a decorative sheet having a total thickness of 130 μm.
[0173] <Example 32> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the following light stabilizer was added to the ionizing radiation curable resin of Example 4. Light stabilizer Product name: Tinuvin 123 (manufactured by BASF) Blend: 1 part by mass.
[0174] <Example 33> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the following light stabilizer was added to the ionizing radiation curable resin of Example 4. Light stabilizer Product name: Tinuvin 123 (manufactured by BASF) Blend: 3 parts by mass.
[0175] <Example 34> A decorative sheet having a total thickness of 130 μm was obtained in the same manner as in Example 4, except that the following light stabilizer was added to the ionizing radiation curable resin of Example 4. Light stabilizer Product name: Tinuvin 123 (manufactured by BASF) Blend: 5 parts by mass.
[0176] <Evaluation> Each of the above decorative sheets was subjected to the evaluations described below. (1) Thickness of the surface protective layer 5 The thickness of the surface protective layer 5 was measured as follows. The decorative sheet was embedded in a resin such as a cold-curing epoxy resin or a UV-curing resin and fully cured, then cut so that the cross section of the decorative sheet appeared, and mechanically polished to obtain a measurement surface. The thickness of the surface protective layer 5 was then measured using a scanning electron microscope SIGMA500 manufactured by Carl Zeiss Microscopy. The length was measured at any 25 points, and the average length measurement value of the 25 points was defined as the "thickness t of the surface protective layer". The measurement conditions were an acceleration voltage of 0.5 keV (low acceleration voltage), a shooting mode of SE2 mode, and a magnification of 2000 times. No sputtering was performed on the measurement sample. The "thickness t of the surface protective layer" was equal to the thickness of the coating film made of the coating liquid for the surface protective layer. In addition, the total thickness of the decorative sheets in Examples 1 to 3 and Comparative Examples 1 to 2 was equal to the sum of the thickness of the surface protective layer 5 and the thickness of the original fabric layer 2. The total thickness of the decorative sheets in Examples 4 to 34 and Comparative Examples 3 to 13 was equal to the sum of the thickness of the surface protective layer 5 , the thickness of the transparent resin layer 4 , the thickness of the adhesive resin layer 4 b and the thickness of the base fabric layer 2 .
[0177] (2) Surface condition The surface condition was evaluated visually for surface uniformity. The evaluation criteria were as follows. 〇: Uniform surface condition △: Some unevenness ×: The surface condition is uneven all over.
[0178] (3) Glossiness The glossiness was measured at 60 degrees using a Rhopoint IQ (manufactured by Konica Minolta, Inc.) The "60° glossiness" in the following table indicates this 60° glossiness.
[0179] (4) Fourier-type infrared spectroscopy For the Fourier infrared spectroscopy, a JASCO Fourier infrared spectrometer (FT / IR-6300) and a single reflection type (incident angle 45°) ATR unit (ATR PRO470-H) with a diamond prism with a sample contact area of 2 mmφ were used.
[0180] The measurement conditions were as follows: Measurement wave number range: 4000cm -1 From 400cm -1 Resolution: 4.0cm -1 Light source: Standard light source Detector: TGS Sample chamber: Standard Sensitivity (gain): 32x Aperture diameter: 7.1mm Interferometer measurement (scan speed): 2mm / sec Filter: 10000Hz Beam splitter: Ge / KBr Apodization function: Cosine Zero Filling: The optical system was purged with nitrogen and the absorption spectrum was obtained by integrating 160 times. Before measuring the absorption spectrum of the sample, background measurement was performed under the same conditions as the sample, except that nothing was brought into contact with the diamond prism and the measurement was performed by integrating 320 times.
[0181] The obtained absorption spectrum was corrected by ATR using the "deep penetration depth" method using Spectra Manager Version 2 manufactured by JASCO Corporation. 1095 / I 1725The value of I was calculated. 1095 is 1095±10cm -1 It refers to the maximum absorbance of the peak detected in the wavenumber range of I 1725 is 1725±10cm -1 This refers to the maximum absorbance of the peak detected in the wavenumber range.
[0182] (5) Fingerprint resistance To evaluate fingerprint resistance, a fingerprint wiping evaluation was performed. The 60° gloss of the surface of each decorative sheet was measured and recorded as "initial gloss". Next, a fingerprint resistance evaluation liquid was applied to the outermost layer, and then the fingerprint resistance evaluation liquid that had been applied to the surface of the decorative sheet was wiped off. Thereafter, the 60° gloss of the portion from which the fingerprint resistance evaluation liquid had been wiped off was measured and recorded as "gloss after wiping". Here, a higher fatty acid was used as the fingerprint resistance evaluation liquid.
[0183] The fingerprint removal rate was calculated using the following formula: Fingerprint removal rate (%) = (glossiness after wiping / initial glossiness) x 100 The evaluation criteria were as follows. AA: 70% or more but less than 250% A: 50% or more but less than 70%, or 250% or more but less than 300% B: Less than 50% or more than 300%.
[0184] (6) Resistance to contamination To evaluate stain resistance, the stain A test specified in the Japanese Agricultural Standards (JAS) was conducted. That is, on the surface protective layer of each decorative sheet, a line of 10 mm width was drawn with blue ink, black quick-drying ink, and red crayon, and left for 4 hours. After that, the blue ink, black quick-drying ink, and red crayon lines were wiped off with a cloth soaked in ethanol, and the stain resistance by ink was evaluated.
[0185] The evaluation criteria were as follows. AA: Lines of each color could be easily wiped off. A: Some of the lines of each color can be wiped off, but some stains remain. B: The lines of each color cannot be wiped off.
[0186] (7) Scratch resistance: Steel wool rubbing test The resulting decorative sheet was attached to wood substrate B using a urethane adhesive, and then a steel wool rubbing test was carried out to evaluate scratch resistance. Specifically, a load of 100 g was applied to the steel wool and the sheet was rubbed back and forth 20 times, and the surface of the decorative sheet was visually inspected for scratches and changes in gloss.
[0187] The evaluation criteria were as follows. AA: No scratches or changes in gloss occurred on the surface. A: Minor scratches or changes in gloss have occurred on the surface. B: Significant scratches or changes in gloss occurred on the surface.
[0188] (8) Processability To evaluate workability, a bending workability test was conducted. In the bending workability test, each sheet was attached to a wood board, and a V-shaped groove was made on the other side of the board up to the boundary where the board and decorative sheet were attached, so as not to scratch the decorative sheet on the other side. Next, the board was bent 90 degrees along the V-shaped groove so that the surface of the decorative sheet formed a mountain fold, and the bent part of the surface of the decorative sheet was observed using an optical microscope to see if there was any whitening or cracks, and the state of bending workability was evaluated.
[0189] The evaluation criteria were as follows: A rating of "A" or higher was deemed to be satisfactory for practical use. AA: No whitening or cracks are observed. A: Some bleaching is visible. B: Whitening is visible over the entire surface or cracks are visible in some areas.
[0190] (9) Weather resistance: Super UV tester The appearance of the decorative sheet after the accelerated weathering test was visually evaluated according to the following criteria. The accelerated weathering test was performed using an Eye Super UV Tester (SUV-W161; manufactured by Iwasaki Electric Co., Ltd.) at a black panel temperature of 63° C. and an illuminance of 65 mW / cm 2One cycle consisted of 20 hours of UV irradiation and 4 hours of condensation. After 30 cycles (720 hours), the appearance of the decorative sheet was visually evaluated.
[0191] The evaluation criteria were as follows. AA: No change in appearance of decorative sheet A: Whitening is observed on the decorative sheet. B: Cracks are observed in the decorative sheet.
[0192] (10) Skin feel The skin feel was evaluated by the following method. First, we carried out advance preparations to ensure that the evaluation criteria were consistent among the evaluators. Specifically, three standard test pieces with different surface properties were prepared. Next, five evaluators were blindfolded and asked to slide their fingers over the surface of the standard test pieces while pressing them with their fingers, and then to classify the tactile sensations into the following three groups. Group 1: Almost no resistance was felt when pushing, but the surface of the decorative sheet felt as if it was sticking to the fingers, and it felt smooth to the touch. Overall, the impression of a smooth texture was strong. In other words, a smooth texture was felt. Group 2: Almost no resistance was felt when pushing, but the surface of the decorative sheet felt as if it was sticking to the fingers. However, there was no impression of a smooth feel. In other words, a moist feel was felt. Group 3: They felt resistance to pressure and also felt the presence of unevenness, i.e., a rough texture.
[0193] The above procedure was repeated until the ratings by each evaluator were consistent for three or more consecutive evaluations, and the ratings between the evaluators were consistent for three consecutive evaluations.
[0194] Next, for each of the decorative sheets, each of the evaluators was blindfolded and pressed the surface of the surface protective layer with a finger while sliding the finger over the surface, and then the tactile sensation was classified into the above three groups. This procedure was repeated until the evaluations by each evaluator were consistent three or more times in a row, and the evaluation results between the evaluators were consistent three times in a row. From the results, the skin sensation was evaluated according to the following criteria. A (Smooth): Group 1 B (moist): Group 2 C (rough): Group 3. The evaluation results are shown in the table below. In the table, if the evaluation result of skin feel is A (smooth), it is indicated by entering the letter Y in the "A (smooth)" column, if the evaluation result of skin feel is B (moist), it is indicated by entering the letter Y in the "B (moist)" column, and if the evaluation result of skin feel is C (rough), it is indicated by entering the letter Y in the "C (rough)" column.
[0195] (11) Cutting level difference Rdc of the transparent resin layer, and cutting level difference Rdc of the surface protective layer and the ratio Rdc / t The cut level difference Rdc of the transparent resin layer was determined before the formation of the surface protective layer as described in the detailed description. The cut level difference Rdc and the ratio Rdc / t of the surface protective layer were determined after the production of the decorative sheet as described in the detailed description.
[0196] [Table 1]
[0197] [Table 2]
[0198] [Table 3]
[0199] [Table 4]
[0200] [Table 5]
[0201] [Table 6]
[0202] [Table 7]
[0203] [Table 8]
[0204] [Table 9]
[0205] [Table 10]
[0206] [Table 11]
[0207] [Table 12]
[0208] As shown in the table, the decorative sheets according to Examples 1 to 34 gave the evaluators a moist feel. The decorative sheets according to Examples 1 to 34 also had low gloss and were excellent in fingerprint resistance, stain resistance, scratch resistance, processability, and weather resistance. In particular, the decorative sheets according to Examples 4 to 34, which include a transparent resin layer, were able to further improve scratch resistance and weather resistance.
[0209] As shown in the table, Comparative Examples 1, 2, 4, 5, 9, 12, and 13 did not give the evaluators a moist feel, but rather a smooth feel, while Comparative Examples 3, 6, 7, 8, 10, and 11 did not give the evaluators a moist feel, but rather a rough feel. [Explanation of symbols]
[0210] Reference Signs List 1: decorative sheet, 2: base fabric layer, 3: pattern layer, 4: transparent resin layer, 4a: embossed pattern, 4b: adhesive resin layer, 5: surface protection layer, 5A: core portion, 5B: ridged portion, 6: primer layer, 11: decorative material, B: substrate
Claims
1. A base fabric layer and a surface protective layer provided on one surface of the base fabric layer, a concave-convex structure including a plurality of ridge-like portions each protruding in a ridge shape is provided on a surface of the surface protection layer; The uneven structure of the surface protective layer has a ratio Rdc / t of a cut level difference Rdc to a thickness t of the surface protective layer of 0.15 or more and 0.44 or less, The thickness t of the surface protective layer is 2 μm or more and 18 μm or less, The absorption spectrum obtained by Fourier infrared spectroscopy of the surface protective layer has a wavelength of 1085 to 1105 cm -1 Maximum value in the wave number range I 1095 and 1715 to 1735 cm -1 Maximum value in the wave number range I 1725 Comparison with I 1095 / I 1725 A decorative sheet having a value of 0.65 or more.
2. 2. The decorative sheet according to claim 1, wherein the surface protective layer has a glossiness of less than 10.
0.
3. 3. The decorative sheet according to claim 1, wherein the ratio Rdc / t is 0.15 or more and 0.31 or less.
4. 4. The decorative sheet according to claim 1, wherein the ratio Rdc / t is 0.15 or more and 0.25 or less.
5. The ratio I 1095 / I 1725 5. The decorative sheet according to claim 1, wherein the .lambda. is 3.5 or less.
6. The decorative sheet according to any one of claims 1 to 5, wherein the surface protection layer comprises a cured resin and particles, the particles having an average particle size of 3 μm or more and 11 μm or less, and the particles are contained in the surface protection layer in an amount of 3 parts by mass or more and 11 parts by mass or less per 100 parts by mass of the resin.
7. 7. The decorative sheet according to claim 6, wherein the resin is an ionizing radiation curable resin.
8. 8. The decorative sheet according to claim 6, wherein the resin is an acrylate.
9. 9. The decorative sheet according to claim 6, wherein the resin is a trifunctional acrylate containing a repeating structure, and the number of repetitions of the repeating structure is 3 or more and 20 or less.
10. 9. The decorative sheet according to claim 6, wherein the resin is a tetrafunctional acrylate containing a repeating structure, and the number of repetitions of the repeating structure is 20 or more and 35 or less.
11. 11. The decorative sheet according to claim 1, further comprising a design layer between said base layer and said surface protective layer.
12. A decorative sheet according to any one of claims 1 to 11; A substrate to which the decorative sheet is attached; A cosmetic material comprising:
Citation Information
Patent Citations
Decorative material
JP2019119138A
Matte article and method for manufacturing same
JP2022008024A
makeup sheet
JP3271022B2
Matte article and method for producing matte article
WO2021201105A1
Matted article
WO2022054644A1